AN ANALYSIS OF SOCIAL CONFLICT IN TOER’S “MIDAH, SIMANIS BERGIGI EMAS” - Rezkiany, Miftha Aulia; Rusmana, Erik; Thamrin, Husni; Harnady, Kunkun K. (IPI Garut Press, 2021)
The title of this research is An Analysis of Social Conflict in Toer’s “Midah, Simanis Bergigi Emas”. This research attempts to analyze the social conflict in the novel and how the author conveyed the social conflict. This research used a descriptive qualitative method in order to answer the research question and used A. J. Greimas theory namely “Actant Scheme and Functional Structure” to process the data. Greimas’s theory used in this research is aim to know the structure of the story and how the conflict happen, because this theory shows the character and the story have a function that interplay with each other such as subject, object, sender, receiver, opponent, and helper. And the result from this research, the researcher found the conflict occurred in the story by the characters connected to the theory used. The researcher choose the book because the story contained in the work mostly talk about social life. Through this research, it can concluded that through literature, the author conveyed their opinion and message about social life and social conflict. In this research, the researcher found that the author conveyed the social conflict based on its acts of characters, sequences of events, and conversations between the characters.